Photoluminescence and Photocatalytic Properties of Ag3PO4 Microcrystals: An Experimental and Theoretical Investigation - Botelho, Gleice; Andres, Juan; Gracia, Lourdes; Matos, Leandro S.; Longo, Elson [UNESP] (Wiley, 2016)
The structural, morphological, and optical properties of Ag3PO4 microcrystals were systematically characterized by using a combination of theoretical calculations and experimental techniques. These microcrystals were synthesized by the microwave-assisted hydrothermal (MAH) method. XRD, Rietveld refinements, and FTIR spectroscopy were employed to carry out a structural analysis; the morphologies of the microcrystals were examined by FEG-SEM. First-principles computational studies were used to calculate the geometries of bulk Ag3PO4 and its (010), (100), (001), (110), (101), (011), and (111) surfaces. A continuous decrease in the energy of the (100) surface led to a good agreement between the experimental and theoretical morphologies. Optical properties were investigated by UV/Vis spectroscopy and photoluminescence (PL) measurements, which revealed a maximum PL emission at λ=444 nm. The MAH-synthesized sample exhibited good activity for the photocatalytic degradation of methyl orange dye under visible irradiation. The photocatalytic activity and PL behavior were correlated with the observed morphology.
Keywords: crystal growth; density functional calculations; photochemistry; silver; surface analysis